Can the United States set rules for the world? - STERN, Brigitte (1997)
Argues that in order to implement their world-wide policy, the United States systematically adopts what are called unilateral 'economic sanctions' that impair the rights or interests of other States. Questions whether the Helms-Burton Act is admissible under international law.